Classiﬁcation of damaged vegetation areas using convolutional neural network over satellite images - Haque, Samiha; Rahman, Nazibur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.